2016
DOI: 10.4236/sgre.2016.79019
|View full text |Cite
|
Sign up to set email alerts
|

Valuation and Determination of Seven and Five Parameters of Photovoltaic Generator by Iterative Method

Abstract: The mathematical modeling of solar cells is essential for any optimization operation of the efficiency or the diagnostics of the photovoltaic generator. The photovoltaic module is generally represented by an equivalent circuit whose parameters are experimentally calculated by using the characteristic current-tension, I-V. The precise determination of these parameters stays a challenge for the researchers, what led to a big diversification in the models and the digital methods dedicated to their characterizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…In their study, the differences between the models were analyzed in terms of accuracy and execution time, and it has been concluded that the two-diode model has better accuracy, but it also has a longer execution time. Similarly, in another study [12], the authors solved both models using a numerical solution on a PV module simulated in a hybrid system. In addition, the authors stated that the single-diode model has fewer parameters so that the unknowns can be calculated in a shorter time, and that the two-diode model is more consistent in terms of accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the differences between the models were analyzed in terms of accuracy and execution time, and it has been concluded that the two-diode model has better accuracy, but it also has a longer execution time. Similarly, in another study [12], the authors solved both models using a numerical solution on a PV module simulated in a hybrid system. In addition, the authors stated that the single-diode model has fewer parameters so that the unknowns can be calculated in a shorter time, and that the two-diode model is more consistent in terms of accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches, 3 and 4 give reasonable results when applied in Equations ((27), (28), (29) and (36)). Evidently, Equations ( 27and (29)) that have been derived at maximum power point and combination of maximum power point and short circuit equations, respectively, give the best results of ∆P mpp error for all saturation current equations at constant ideality factor.…”
Section: Approachmentioning
confidence: 79%
“…This category gives satisfactory Again, the data shown in Table 3 & Table 4 in rows 9 -12, represent category 3 where I o is determined using Equation (17). This category gives satisfactory [R s , R sh ] pair only from Equations ((27), (28), (29) and (36)).…”
Section: Approachmentioning
confidence: 94%
See 2 more Smart Citations